2012
DOI: 10.1093/nar/gks1130
|View full text |Cite
|
Sign up to set email alerts
|

Human mitochondrial RNA decay mediated by PNPase–hSuv3 complex takes place in distinct foci

Abstract: RNA decay is usually mediated by protein complexes and can occur in specific foci such as P-bodies in the cytoplasm of eukaryotes. In human mitochondria nothing is known about the spatial organization of the RNA decay machinery, and the ribonuclease responsible for RNA degradation has not been identified. We demonstrate that silencing of human polynucleotide phosphorylase (PNPase) causes accumulation of RNA decay intermediates and increases the half-life of mitochondrial transcripts. A combination of fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
182
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(217 citation statements)
references
References 71 publications
6
182
1
2
Order By: Relevance
“…Here, we revealed that Dss1 interacts specifically with the large ribosomal subunit, whereas Suv3 is mainly a component of the nucleoid-MIOREX complex, in line with previous observations that it copurifies with mitochondrial ribosomes (Dziembowski et al, 2003) and a cluster-like organization adjacent to RNA and DNA (Borowski et al, 2013). The interaction of an RNase with the ribosome is reminiscent of the situation in bacteria, where RNase R binding to the small ribosomal subunit (Malecki et al, 2014) both stabilizes the enzyme and sequesters it from undesired spontaneous nucleolytic activity (Liang and Deutscher, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we revealed that Dss1 interacts specifically with the large ribosomal subunit, whereas Suv3 is mainly a component of the nucleoid-MIOREX complex, in line with previous observations that it copurifies with mitochondrial ribosomes (Dziembowski et al, 2003) and a cluster-like organization adjacent to RNA and DNA (Borowski et al, 2013). The interaction of an RNase with the ribosome is reminiscent of the situation in bacteria, where RNase R binding to the small ribosomal subunit (Malecki et al, 2014) both stabilizes the enzyme and sequesters it from undesired spontaneous nucleolytic activity (Liang and Deutscher, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Several recent studies in mammalian cells have shown that RNA degradation and newly transcribed RNA are found in foci that are located in vicinity to the mitochondrial DNA (Antonicka et al, 2013;Borowski et al, 2013;Jourdain et al, 2013;Lee et al, 2013). These RNA granules also contain RNA-binding proteins, methyltransferases, and ribosomal proteins, therefore likely representing the nucleoid-MIOREX complexes identified here.…”
Section: Discussionmentioning
confidence: 54%
“…At least three distinct types of foci relevant to mtDNA expression have been identified and visualized within the mitochondrial matrix of human cells. Those are the mitochondrial nucleoids, RNA granules and the RNA degradosome [156]. Here we will discuss the available data suggesting that the nucleoid and the RNA granule could be the factories where mitoribosomes are assembled.…”
Section: Nucleoids Rna Granules and Mitoribosome Assemblymentioning
confidence: 99%
“…Western blotting was performed similar to the description by Ford et al (9), and all antibodies were purchased from Cell Signaling. ATP concentration was determined in freeze-clamped liver tissue according to the manufacturer's instruction (ab113849; Abcam) (30).…”
Section: Analytical Measurementsmentioning
confidence: 99%